ISOLAMENTO E SELEÇÃO DE FUNGOS PREDADORES DE NEMATÓIDES - Alcântara, Vânia Silvia Bardauil; Azevedo, João Lúcio de (REVISTA DE AGRICULTURA, 2015)
ISOLAMENTO E SELEÇÃO DE FUNGOS PREDADORES DE NEMATÓIDES